Coumarin-heterocycle framework: A privileged approach in promising anticancer drug design - Atukuri Dorababu (Elsevier, 2021)
The cancer cases are increasing in fast pace; most of them are resulted from exposure to harmful pollutants. Genetic factors are responsible for cancer only to a small extent. Prevention and cure of cancer should be considered as a high priority because of severity of cancer-related issues. Some cancer types caused by microbes may be prevented by vaccines. However, possibility of vaccine-development for other cancer types is very scarce. Hence, chemotherapeutic regimens have been developed for treatment of cancer. There are very serious side effects and drug-resistance arising from chemotherapy. So, the research to be undertaken is drug-discovery for cancer treatment associated with least side effects. The research literature infers that coumarin derivatives are promising pharmacological agents. Particularly, coumarin analogs are shown to be potent antitumor agents with low cytotoxicity. Also, coumarin-heterocycle hybrid approach has been resulted in efficient anticancer agents. Hence, anticancer activity of coumarin-heterocycle derivatives reported recently is compiled and evaluated critically. The review is organized based on type of heterocycle appended to coumarin moiety. Also, with structure-activity relationship, antitumor activity of various coumarin analogs has been discussed. This work would aid researchers in identifying promising antitumor molecules.